Benefit of addition of clopidogrel in addition to aspirin and fibrinolytic therapy in STEMI: an Indian data - Kannan, Abhilash; Chandrasekharan, Rajasekharan; Velayudhan, Radhakrishnan Vallikkattu (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The study was designed to find out whether the addition of clopidogrel for patients with ST- elevation myocardial infarction [STEMI] who are receiving a standard fibrinolytic therapy, including aspirin, reduce the incidence of primary and secondary end points like recurrent ischemia, re-infarction, need for urgent Target Vessel Revascularisation [TVR], mortality & bleeding. Methods: The patients were randomly assigned to receive the study medication. The patients were divided into two groups. Those receiving fibrinolytic therapy & aspirin were included in Group A. Those receiving the study drug in addition to aspirin & fibrinolytic agent were included in Group B. The study drug was given daily upto 1 month. These patients were assessed during their hospital stay & followed up for a period of 30 days for end points like recurrent ischemia, re-infarction, need for urgent TVR, bleeding episodes & mortality. Results: There was reduction in primary endpoints in group B compared to group A of which only reduction of recurrent ischemia was statistically significant (26% vs 2%). The same pattern of benefit was seen with secondary end points with significant reduction in recurrent ischemia in group B (28% vs 2%). Safety end points showed some increased bleeding in group B patients which was statistically insignificant (4% vs 0). Conclusion: Addition of Clopidogrel to aspirin and fibrinolytic therapy in ST-elevation MI showed a significant reduction in recurrent ischemia during in hospital stay and during the first 30 days. The patients received clopidogrel had less mortality compared to aspirin group. There were only minor bleeding episodes reported with use of clopidogrel.